Kombinasi Metode Rank Order Centroid dan Operational Competitiveness Rating Analysis Dalam Seleksi Penerimaan Staff Perpustakaan - Agung Deni Wahyudi; Ari Sulistiyawati (Journal of Artificial Intelligence and Technology Information (JAITI), 2024)
Library staff are personnel who work in libraries and are responsible for managing, organizing, and providing various information services to library users. This selection process usually involves several stages, ranging from meeting administrative requirements to assessing the technical and interpersonal abilities of prospective staff. Problems that occur in the selection that do not have clear assessment guidelines can lead to highly subjective assessments, where decisions are influenced more by personal opinion than objective criteria. The purpose of this study is to apply a more objective, structured, and targeted approach to the selection of library staff admissions through a combination of ROC and OCRA methods that produce a selection model that can be applied to various library institutions, as well as support the improvement of service quality and library management through the selection of qualified staff. The results of the evaluation using the OCRA method, the candidate with the highest final score was Candidate H with a score of 0.9133, which placed him in the first rank as the most suitable candidate for the position of library staff. Candidate E was ranked second with a score of 0.8339, showing almost comparable performance and also very competitive. In third place is Candidate B with a final score of 0.3578. The results of this ranking help in identifying the best candidates and show qualitative differences between each prospective staff, supporting the decision-making process in the admission of library staff.